An Exploratory Study on the Impact of Physical Training on Police Recruits' Self-Efficacy in Handling Violent Encounters. Issue 13 (1st February 2023) - Butler, Jeremy M.; Gothe, Neha; Petruzzello, Steven
Abstract : Police officers are often required to use physical force to effectively protect themselves as well as the public. In order to prepare officers for these physical demands, recruits receive training in fitness and defensive tactics during their Police Academy instruction. The present study aimed to develop a reliable scale for measuring an officer's self-efficacy and used the scale to evaluate the impact of the Academy training on recruits' self-efficacy. Most of the participants credited the academy control tactics (98.5%) and fitness training (88.1%) with improving their self-efficacy. These results support the importance of physical training curricula at improving recruit officers' self-efficacy toward handling violent encounters prior to entering the law enforcement workforce.